Early history of the Southwest through the eyes of German-speaking Jesuit missionaries : a transcultural experience in the eighteenth century - Classen, Albrecht (Lexington Books, 2013)
This book provides unique and lively, authentic, and source-based insights into the history, culture, geograpyh, fauna, flaura, geology, climate, and politics of eighteenth-century Sonora/Arizona, drawing from the fascinating first-hand accounts written by German speaking Jesuit missionaries. Transcultural experiences of extraordinary kinds dominate those accounts which allow us to understand the difficult, problematic, sometimes hostile, but then also productive and fruitful contacts, interactions, and dealings between the European missionaries and the native population.</sp.